PENGELOLAAN SAMPAH KALA COVID-19 - Widyaningsih, Niluh; Cahya, Darmawan L; Suprajaka, Suprajaka (Universitas Esa Unggul, 2020)
Household waste management changed drastically due to Covid-19 global pandemic. This Covid-19 adds the household consumption for health masks and it increases the solid waste number. People must wear the health mask that covers the nose and mouth if they do outside activities. This health mask becomes the most demanding item in the market but not enough supply. It increased the price badly and make people buying it irrationally. The used masks create another issue on the solid waste household. This waste is different from organic waste and inorganic waste. It has different solid waste management system too. We must separate the waste from the rest of the household solid waste by cutting the used health masks and put it in a plastic before we put it in the trash bin in front of our house. The special care for this infectious waste could help the safety workers and other people for not being sick from the Covid-19. It can help to reduce the number of household solid waste before it goes to the temporary landfills (TPS) and landfills (TPA). It needs change in waste managementÃ¢â‚¬â„¢s culture for Indonesian to support the household solid waste (including the infectious waste).Ã‚Â Keywords : waste management, covid-19